Respiratory Frequency of Children with Asthma Using Superbubbles Blood Intervention - J, Harsismanto; Padila, Padila; Andri, Juli; Andrianto, Muhammad Bagus; Sartika, Andry (JOSING: Journal of Nursing and Health, 2021)
This study aimed to compare blowing bubbles blades to the respiratory frequency of children with asthma in the Edelweiss Room, DR. M. Yunus Bengkulu Year 2019. The research design used was quasi-experimental research. The univariate analysis results showed that the average respiratory rate before and after super bubble blow therapy was moderate (26.91). Before and after blowing the propeller, the intermediate respiratory frequency was medium (26.69) and light (24.81). The bivariate analysis results showed an effect of blowing bubbles on respiratory frequency in children with a value of p = 0.000. In conclusion, there is no difference in superbubbles blowing therapy's effectiveness by blowing bamboo propellers in children with asthma. Keywords: Respiratory Frequency, Blow Super Bubbles